HUBUNGAN PERILAKU KEPEMIMPINAN DENGAN MOTIVASI KERJA - Yuswa Eko Prayoga E.42008059 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This journal is titled “The Relationship between the Leadership’s Behavior with the Sub-district Employee Motivation” in which the research is located at the Head Office of Samalantan of Bengkayang Regency for acquairing the Sarjana Degree of School of Government at Tanjungpura University of Government Department cooperated with the Government of West Kalimantan with Tanjungpura University. This journal is purposed to find the relationship of the trait of a leadership with the employee’s motivation. This journal is aimed to investigate the relationship between the leadership’s behavior with the Sub-district Employee Motivation. The title of the journal was selected based on the issues identified by the researcher in which the Sub-district Employee Motivation in the institutions surveyed still believed to be less able to support the tasks of the organisation. The research published in this journal is using explanative research methods with quantitative approaches. The research was divided into two phases; identifiers problems phase and testing of the relevance phase in those toward the problem of existing theories embodied by the researchers to see whether or not the Relationship Between Leadership Behavior of Sub-district Leader with Sub-district Employee Motivation and make recommendations of leadership strategies that motivate in which it is based on the theory. The subjects of the research were Samalantan Sub-district Head Office of the respondents were all employees in there. The conclusion of this paper is based on quantitative data processing using the statements of the respondents were analyzed quantitatively, it appears there is a relationship between Sub-district Leadership Behavior with the Employees Motivation at Sub-district Head Office of Samalantan in that the correlation level is moderate. Therefore, it is expected to keep the sub-district leadership behavior to employees in order to increase employee motivation. Keywords: Quantitative Approach, Leadership Behavior, Motivation, Relationship.